Danno da nascita indesiderata e danno da nascita malformata: la parola alle Sezioni Unite (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
This contribution is focused on the main questions involving claims for damages about wrongful birth and wrongful life. The Italian jurisprudence is divergent in drawing the most balanced solutions about evidence and causation: a decision of the Joined Chambers of the Court of Cassation is now awaited.
Keywords: wrongful birth; wrongful life; self-determination; claim for damages; evidence; causation